Non‐linear modelling and distortion compensation in optical Fast‐orthogonal frequency division multiplexing systems - Luis Carlos Vieira; Waseem Ozan; John Mitchell; Izzat Darwazeh (IET Optoelectronics, 2023)
Abstract Fast‐OFDM‐based intensity‐modulation and direct‐detection (IM/DD) has been proposed for deployment of cost‐efficient optical access networks, due to its implementation simplicity and high spectral efficiency. In this article, the accuracy of the generalised memory polynomial (GMP) for the non‐linear modelling of optical Fast‐OFDM links is studied, including memory effects and considering different model parameters. After model validation using measured data of a 10 km single mode fibre link, the GMP is used for performance investigations of a distortion compensation approach to optical Fast‐OFDM, for up to 16PAM modulation formats and different number of Fast‐OFDM subcarriers. This study firstly reports the performance results of optical 16PAM‐Fast‐OFDM systems using either 2PAM‐ or 4PAM‐based training signals for digital post‐distortion and FFT‐based channel estimation, and firstly investigates the influence of the zero padding (ZP) length on the performance of optical Fast‐OFDM. Excellent performance improvements are achieved using the proposed distortion compensation scheme, relative to conventional system implementation.